Clinical Use of Intravenous Fosfomycin in Critical Care Patients in Taiwan - Tzu-Ting Chen; Yun-Fu Chang; Yea-Chwen Wu (Pathogens, 2023)
This retrospective study aimed to evaluate the clinical use and side effects of fosfomycin in critically ill patients in Taiwan. Forty-two patients (mean age, 69.9 years; female, 69%) who received fosfomycin were included from a teaching hospital in Taiwan from January 2021 to December 2021. We analyzed the prescription pattern of intravenous fosfomycin and evaluated patient safety profiles, clinical successes, and microbiological cure rates. The main indication was urinary tract infections (35.6%), and the most frequently identified pathogen was Escherichia coli (18.2%). The overall clinical success was 83.4%, with one multidrug-resistant pathogen isolated from eight patients (19.0%). The average dose of fosfomycin given was 11.1 ± 5.2 g/day. The average duration of therapy was 8.7 ± 5.9 days, with a median duration of 8 days, where fosfomycin was mostly (83.3%) given in combination. Fosfomycin was given 12 hourly to a maximum number (47.6%) of cases. The incidence rates of adverse drug reactions (hypernatremia and hypokalemia) were 33.33% (14/42) and 28.57% (12/42), respectively. The overall survival rate was 73.8%. Intravenous fosfomycin may be an effective and safe antibiotic to use in combination with other drugs for empirical broad-spectrum or highly suspected multidrug-resistant infections in critically ill patients.